A dual-action niclosamide-based prodrug that targets cancer stem cells and inhibits TNBC metastasis - Ji Hyeon Kim; Soeun Park; Eunsun Jung; Jin Woo Shin; Yoon-Jae Kim; Ji Young Kim; Jonathan L. Sessler; Jae Hong Seo; Jong Seung Kim (2023)
Chemotherapy typically destroys the tumor mass but rarely eradicates the cancer stem cells (CSCs) that can drive metastatic recurrence. A key current challenge is finding ways to eradicate CSCs and suppress their characteristics. Here, we report a prodrug, Nic-A, created by combining a carbonic anhydrase IX (CAIX) inhibitor, acetazolamide, with a signal transducer and transcriptional activator 3 (STAT3) inhibitor, niclosamide. Nic-A was designed to target triple-negative breast cancer (TNBC) CSCs and was found to inhibit both proliferating TNBC cells and CSCs via STAT3 dysregulation and suppression of CSC-like properties. Its use leads to a decrease in aldehyde dehydrogenase 1 activity, CD44high/CD24low stem-like subpopulations, and tumor spheroid-forming ability. TNBC xenograft tumors treated with Nic-A exhibited decreased angiogenesis and tumor growth, as well as decreased Ki-67 expression and increased apoptosis. In addition, distant metastases were suppressed in TNBC allografts derived from a CSC-enriched population. This study thus highlights a potential strategy for addressing CSC-based cancer recurrence.